Draft Annual Plan 1979-80 Haryana State (In 4 Volumes) - Planning Commission (Planning Commission, 1979)
The main thrust of the plan programme in the year 1979-80 would he on the cost of liquation of the facilities already created, modernisation of the existing canal systems for improved efficiency, expeditious completion of schemes in the drought prone area and expansion of irrigated agriculture through conductive use of ground water and surface water. The State has executed lift irrigation schemes during the current plan period for extending irrigation to the drought prone areas. These systems would he able to provide the contemplated benefits only when the State is able to receive its share of surplus Ravi- east waters.
Planning Department, Government of Haryana